Maintained Serum Sodium in Male Ultra-Marathoners – The Role of Fluid Intake, Vasopressin, and Aldosterone in Fluid and Electrolyte Regulation - Bürge, J.; Knechtle, B.; Knechtle, P.; Gnädinger, M.; Rüst, C. A.; Rosemann, T. (Hormone and Metabolic Research, 2011)
Exercise-associated hyponatremia (EAH) is a well know electrolyte disorder in endurance athletes. Although fluid overload is the most like etiology, recent studies, however, argued whether EAH is a disorder of vasopressin secretion. The aims of the present study were to investigate (i) the prevalence of EAH in male ultra-marathoners and (ii) whether fluid intake, aldosterone or vasopressin, as measured by copeptin, were associated with post-race serum sodium concentration ([Na+]). In 50 male ultra-marathoners in a 100 km ultra-marathon, serum [Na+], aldosterone, copeptin, serum and urine osmolality, and body mass were measured pre- and post-race. Fluid intake, renal function parameters and urine excretion were measured. No athlete developed EAH. Copeptin and aldosterone increased; a significant correlation was found between the change in copeptin and the change in serum [Na+], no correlation was found between aldosterone and serum [Na+]. Serum [Na+] increased by 1.6%; body mass decreased by 1.9 kg. The change in serum [Na+] and body mass correlated significantly and negatively. The fluid intake of ~ 0.58 l/h was positively related to the change in body mass and negatively to both post-race serum [Na+] and the change in serum [Na+]. We conclude that serum [Na+] was maintained by both the mechanisms of fluid intake and the hormonal regulation of vasopressin.
Keywords: electrolytes; aldosterone; vasopressin; ultra-endurance